CURRENT STATE AND FUTURE PROSPECTS OF CREATIVITY TRAINING MODULES (CTM) IN PUBLIC ART EDUCATION IN CHINESE UNIVERSITIES: A LITERATURE REVIEW - Yang Hong; Norzuraina Mohd Nor; WenKai Zhou; Roslita Ramli, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper provides an overview of the current state and future prospects of creativity training modules (CTM) in public art education in Chinese universities. We begins by introducing the concept and theoretical foundation of CTM, followed by an analysis of the current state of public art education in Chinese universities. The article then delves into the application of CTM in public art education, covering aspects such as curriculum, teaching methods, and interdisciplinary approaches. Additionally, the article highlights the challenges and opportunities faced by CTM in public art education in Chinese universities, including issues such as the lack of a systematic curriculum design, insufficient teaching resources, and low student participation. Finally, we concludes by presenting policy recommendations and suggesting future research directions, aiming to offer insights for promoting the development of CTM in public art education in Chinese universities.